Development and characterization of ceramic-polymeric hybrid scaffolds for bone regeneration: incorporating of bioactive glass BG-58S into PDLLA matrix - Aguiar, Veronica Cristina Pêgo Fiebig (2024)
In recent years, there has been a notable surge of interest in hybrid materials within the biomedical field, particularly for applications in bone repair and regeneration. Ceramic-polymeric hybrid scaffolds have shown promising outcomes. This study aimed to synthesize bioactive glass (BG-58S) for integration into a bioresorbable polymeric matrix based on PDLLA, aiming to create a bioactive scaffold featuring stable pH levels. The synthesis involved a thermally induced phase separation process followed by lyophilization to ensure an appropriate porous structure. BG-58S characterization revealed vitreous, bioactive, and mesoporous structural properties. The scaffolds were analyzed for morphology, interconnectivity, chemical groups, porosity and pore size distribution, zeta potential, pH, in vitro degradation, as well as cell viability tests, total protein content and mineralization nodule production. The PDLLA scaffold displayed a homogeneous morphology with interconnected macropores, while the hybrid scaffold exhibited a heterogeneous morphology with smaller diameter pores due to BG-58S filling. The hybrid scaffold also demonstrated a pH buffering effect on the polymer surface. In addition to structural characteristics, degradation tests indicated that by incorporating BG-58S modified the acidic degradation of the polymer, allowing for increased total protein production and the formation of mineralization nodules, indicating a positive influence on cell culture.